Development of HerbaLens: A Medicinal Plant Image Capture Application - Rivera, Mark Angelo P.; Dubiao, Paul Xavier M.; Villagonzalo, Ariann P.; Dorin, Rommel L.; Barasi, Estela D.V.; Sabado, Wilber B. (International Journal of Computing Sciences Research; Vol 9 (2025): Volume 9, 2025)
Purpose – This study introduces HerbaLens, an Android application developed to assist users in capturing images of medicinal plants in Calauan, Laguna, and retrieving relevant information for identification and educational purposes. The app aims to prevent the misuse and destruction of endangered species while promoting education, conservation, and the preservation of traditional knowledge. Method – The study employs a developmental and descriptive research design. The developmental aspect focuses on refining the app's functionality, user interface, and database to enhance its ability to identify and provide relevant information about medicinal plants accurately. The descriptive aspect collects data on the characteristics and uses of these plants. Results – The application was evaluated using ISO 25010 standards—functionality, usability, reliability, and performance efficiency—and was rated as "Satisfied" by experts. Limited to 23 verified plants and 2,455 datasets, HerbaLens demonstrated strong functionality, high usability, consistent reliability, and commendable performance efficiency. Conclusion - The HerbaLens application has significantly contributed to the community, public health, and plant conservation by aiding in the identification of medicinal plants. Its well-designed interface and frequent updates have helped achieve high accuracy and user satisfaction. Recommendations – The plant database should be updated continuously, and the image recognition algorithms should be improved. Future work may involve increasing user engagement through gamification and the creation of social groups, expanding the application's compatibility with iOS devices, and improving its performance under various conditions. Research Implications – The application is highly useful to the community, students, botanists, and researchers as it provides accurate information that can support further research endeavors. Practical Implications – The offline mode of the application is useful in areas with limited or no internet connection. Social Implications – Through the encouragement of the preservation of traditional knowledge and supporting the conservation causes, HerbaLens benefits the local communities as well as the global conservation causes.